Computed Tomographic Imaging in Connective Tissue Diseases - Barnett, Joseph; Devaraj, Anand (Seminars in Respiratory and Critical Care Medicine, 2019)
Pulmonary disease represents a significant extra-articular manifestation in the majority of connective tissue diseases (CTDs). The identification, classification, and staging of pulmonary involvement are centrally important to the management of patients, aiding the prognostication of disease behavior and treatment decisions. We present a review of the high-resolution computed tomographic pulmonary features of CTD in the lung and their significance to the reporting radiologist.
Keywords: HRCT; connective tissue disease; fibrosis